Rancang bangun Sistem Informasi Reservasi dan Stok Pada Harni Salon Berbasis Web - M. Farhan; Muhammad Zen; Barany Fachri (Jurnal Nasional Teknologi Komputer, 2026)
Beauty salons are service businesses that require precise management of service schedules and product stocks to maintain service quality and customer satisfaction. Manual reservation and stock management has the potential to cause recording errors, schedule conflicts, and product inventory discrepancies. Therefore, this study aims to design and implement a web-based Harni Salon Reservation and Stock Information System. The research methods used include system requirements analysis, system design using modeling diagrams, PHP and MySQL-based system implementation, and functional testing using the black box testing method. The results of the study indicate that the system is able to manage customer data, services, reservations, and product stocks in an integrated manner and displays reservation and inventory report information well. This system also allows customers to make service reservations independently based on available schedules, while the admin can confirm reservations and monitor product stocks in real-time. The conclusion of this study is that the implementation of a web-based information system can improve operational efficiency and service quality at Harni Salon. The benefits of this study are expected to be a reservation and stock management solution for salon businesses and become a reference for the development of similar systems in the future.